Small-pad resistive micromegas for high rate environment: performance of different resistive protection concepts - Alviggi, Mariagrazia; Franchino, Silvia (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2019)
We present the development of resistive Micromegas with small pad readout aiming at precision tracking without efficiency loss up to several MHz/cm2. Several prototypes have been built with the spark protection resistive layer deposited with different techniques: a pad-patterned embedded resistor layout with screen printing, and a uniform layer by sputtering (Diamond Like Carbon structure). All detectors consist of a matrix of 48 × 16 rectangular shaped pads with a pitch of (1 × 3) mm2. The active surface is (48 × 48) mm2 with a total number of 768 channels, routed off-detector for readout. Characterization and performance studies of all prototypes have been carried out by means of radioactive sources, X-rays, cosmic rays and high energy particle beams. A comparison of prototypes with different resistivity layout will be presented.